(8x+7h)(8x+7h)=

Simple and best practice solution for (8x+7h)(8x+7h)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (8x+7h)(8x+7h)= equation:


Simplifying
(8x + 7h)(8x + 7h) = 0

Reorder the terms:
(7h + 8x)(8x + 7h) = 0

Reorder the terms:
(7h + 8x)(7h + 8x) = 0

Multiply (7h + 8x) * (7h + 8x)
(7h * (7h + 8x) + 8x * (7h + 8x)) = 0
((7h * 7h + 8x * 7h) + 8x * (7h + 8x)) = 0

Reorder the terms:
((56hx + 49h2) + 8x * (7h + 8x)) = 0
((56hx + 49h2) + 8x * (7h + 8x)) = 0
(56hx + 49h2 + (7h * 8x + 8x * 8x)) = 0
(56hx + 49h2 + (56hx + 64x2)) = 0

Reorder the terms:
(56hx + 56hx + 49h2 + 64x2) = 0

Combine like terms: 56hx + 56hx = 112hx
(112hx + 49h2 + 64x2) = 0

Solving
112hx + 49h2 + 64x2 = 0

Solving for variable 'h'.

Factor a trinomial.
(7h + 8x)(7h + 8x) = 0

Subproblem 1

Set the factor '(7h + 8x)' equal to zero and attempt to solve: Simplifying 7h + 8x = 0 Solving 7h + 8x = 0 Move all terms containing h to the left, all other terms to the right. Add '-8x' to each side of the equation. 7h + 8x + -8x = 0 + -8x Combine like terms: 8x + -8x = 0 7h + 0 = 0 + -8x 7h = 0 + -8x Remove the zero: 7h = -8x Divide each side by '7'. h = -1.142857143x Simplifying h = -1.142857143x

Subproblem 2

Set the factor '(7h + 8x)' equal to zero and attempt to solve: Simplifying 7h + 8x = 0 Solving 7h + 8x = 0 Move all terms containing h to the left, all other terms to the right. Add '-8x' to each side of the equation. 7h + 8x + -8x = 0 + -8x Combine like terms: 8x + -8x = 0 7h + 0 = 0 + -8x 7h = 0 + -8x Remove the zero: 7h = -8x Divide each side by '7'. h = -1.142857143x Simplifying h = -1.142857143x

Solution

h = {-1.142857143x, -1.142857143x}

See similar equations:

| -2a-3a=-5 | | 6k+5k=-11 | | 6-4x=78 | | -68=-3+5(3x-4) | | 66=4t-15t | | 2(6v-3)=-66 | | 2=x+4+x | | -2x-4+3=9 | | m-5m=-8 | | 84=7(v-79) | | -9+p/2=-12 | | 6+4x=6x-9 | | -7x+9=4x+141 | | 30y+20-3=7 | | 3x-1=-4x+6 | | 8y-4-5=5 | | 2/3(1/2) | | -2+x+7x=-50 | | -w-(3x-3w)+x= | | 3x+1+3x=-53 | | -3=1/3k | | -2u+6=-10 | | t/2-1=2 | | h-90/4=-2 | | -2=h-90/4 | | k-81/8=2 | | -13+8c=27 | | 2v+18=46 | | 2(v-40)=88 | | q/3-(-4)=7 | | 2=3n-1 | | n/2-14=-11 |

Equations solver categories